5X + 6Y - 2Z = 36
X + 5Y - 6Z = 53
4X + 2Y + 9z = 90
TENTUKAN NILAI X, Y, DAN Z !!
nilai X
1. 5x+6y-2z=36
5x-2z-(-2z)=36-(6y)-(-2z)
5x=36-(6y)-(-2z)
5x=-6y+2z+36
x=(-6y+2z+36)×1/5
x=-6y×1/5+2z×1/5+36×1/5
x=-6/5y+2z×1/5+36×1/5
×=-6/5y+2/5z+36×1/5
X=-6/5y+2/5z+36/5
nilai Y
5x+6y-2z=36
6y-2z-(-2z)=36-(5x)-(-2z)
6y=36-(5x)-(-2z)
6y=-5x+2z+36
y=(-5x+2z+36)÷6
y=(-5x+2z+36)×1/6
y=-5x⅙+2z×⅙+36×⅙
y=-⅚x+2z×⅙+36×⅙
y=-⅚x+⅓z+36×⅙
y=-5/6x+1/3z+6
nilai Z
5+6y-2z=36
-2z=36-(5x)-(6y)
-2z=-5x-6y+36
2z=5x+6y-36
z=(5x+6y-36)÷2
z=(5x+6y-36)×1/2
z=5x×½+6y×½-36×½
z5/2x+6y×1/2-36×1/2
z=5/2x+3y-36×1/2
Z=5/2x+3y-18
2. nilai X
x+5y-6z=53
x-6z-(-6z)=53-(5y)-(-6z)
x=53-(5y)-(-6z)
X=-5y+6z+53
nilai Y
"
5y-6z-(-6z)=53-x-(-6z)
5y=53-x-(-6z)
5y=-x+6z+53
y=(-x+6z+53)÷5
y=(-x+6z+53)×1/5
y=-1/5x+6z×1/5+53×1/5
y=-1/5x+6/5z+53×1/5
Y=-1/5x+6/5z+53/5
Nilai Z
"
-6z=53-x-(5y)
-6z=-x-5y+53
6z=x+5y-53
z=(x+5y-53)÷6
z=(x+5y-53)×1/6
z=1/6x+5y×1/6-53×1/6
z=1/6x+5/6y-53×1/6
Z=1/6x+5/6y-53/6
3. nilai x
"soal"
4x=90-(3y)-(9z)
4x=-2y-9z+90
x=(-2y-9z+90)÷4
x=(-2y-9z+90)×1/4
x=-2y×1/4-9z×1/4+90×1/4
x=-1/2y-9z×1/4+90×1/4
x=-1/2y-9/4z+90×1/4
X=-1/2y-9/4z+45/2
nilai Y
"
2y=90-(4x)-(9z)
2y=-4x-9z+90
y=(-4x-9z+90)÷2
y=(-4x-9z+90)×1/2
y=-4x×1/2-9z×1/2+90×1/2
y=-2y-9z×1/2+90×1/2
y=-2x-9/2z(90×1/2
Y=-2x-9/2z+45
nilai Z
"
9z=90-(4x)-(2y)
9z=-4x-2y+90
z=(-4x-2y+90)÷9
z=(-4x-2y+90)×1/9
z=-4x×1/9-2y×1/9+90×1/9
z=-4/9x-2y×1/9+90×1/9
z=-4/9x-2/9y+90×1/9
Z=-4/9x-2/9y+10
SEMOGA MEMBANTU
[tex]{ \colorbox{pink}{ \{{ \boxed{ \boxed{ \colorbox{pink}{{{{ \: answer \: by \: aymtk}}}}}}}}}[/tex]
[answer.2.content]